2023
DOI: 10.3389/fphar.2023.1149185
|View full text |Cite|
|
Sign up to set email alerts
|

Lactobacillus reuteri strain 8008 attenuated the aggravation of depressive-like behavior induced by CUMS in high-fat diet-fed mice through regulating the gut microbiota

Abstract: Objective: Gut microbiota play a key role in the pathogenesis of obesity and depression. Probiotics are a preventive strategy for obesity and a novel treatment for depression symptoms. However, the ameliorative or therapeutic effect of potential probiotic candidate Lactobacillus reuteri (L. reuteri) on obesity and depression comorbidity still remains unclear. We investigated the effects of chronic unpredictable mild stress (CUMS) in high-fat diet-fed mice and the effects of Lactobacillus reuteri strain 8008 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…For example, increased formation and release of KYNA by L. reuteri may regulate the enteric nervous system [75], affect the growth and viability of probiotic bacteria in the digestive system [76], alleviate various gastrointestinal pathologies [77] and have anti-inflammatory effects by inhibiting Th17 cell differentiation and the increase in TNFα in monocytes and leukocytes [20,78]. Notably, though the mechanistic link clearly needs to be investigated further, KYNA generated by L. reuteri-alone or in combination with other probiotics-may also participate in the attenuation of depressive-like symptoms associated with chronic stress [41] and in the reduction of obesity-related behavioral impairments and related microglial activation [42,43,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, increased formation and release of KYNA by L. reuteri may regulate the enteric nervous system [75], affect the growth and viability of probiotic bacteria in the digestive system [76], alleviate various gastrointestinal pathologies [77] and have anti-inflammatory effects by inhibiting Th17 cell differentiation and the increase in TNFα in monocytes and leukocytes [20,78]. Notably, though the mechanistic link clearly needs to be investigated further, KYNA generated by L. reuteri-alone or in combination with other probiotics-may also participate in the attenuation of depressive-like symptoms associated with chronic stress [41] and in the reduction of obesity-related behavioral impairments and related microglial activation [42,43,46].…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus (L.) reuteri, a well-studied probiotic bacterium that colonizes the gastrointestinal tract of both humans and animals, can influence the composition of the gut microbiota [41] and has been shown to exert a remarkable range of beneficial effects in both humans and relevant animal models. Notably, L. reuteri administration affects neurodevelopment and prevents social deficits and depressive-like behaviors in experimental animals [41][42][43][44][45][46][47]. Interestingly, though the underlying mechanisms have not been identified so far, L. reuteri is able to normalize the impaired plasma levels of KP metabolites caused by chronic stress and to improve associated behavioral abnormalities [35].…”
Section: Introductionmentioning
confidence: 99%
“…The WoSCC, recognized for its extensive interdisciplinary scope, hosts over 170 million articles from more than 250 academic disciplines (Shi et al, 2022). Specifically, the database hosts a significant volume of literature pertinent to our study, with a considerable number of articles and cited references directly related to gut microbiota research within the realm of endocrinology and metabolism (Zhang et al, 2022;Li C. et al, 2023;Xue et al, 2023;Takeuchi et al, 2023). Given the database's extensive usage and acclaim in scientometric research, it provides a solid basis for analyzing the trajectory of gut microbiota research in our field.…”
Section: Discussionmentioning
confidence: 99%
“…Building upon this, targeted research has illuminated the roles of specific bacteria. Studies have demonstrated that Lactobacillus reuteri and Akkermansia muciniphila show a negative correlation with serum LPS levels and fasting plasma glucose levels (Shi et al, 2022;Li C. et al, 2023). This indicates these bacteria become a potential therapeutic target for reducing serum LPS levels and improving glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Wu and colleagues found that L. reuteri reconstructed the epithelial integrity by activating the Wnt/bcatenin pathway, thereby promoting the intestine epithelial cell proliferation and inducing intestinal stem cell differentiation to Paneth cells, even under the condition of TNF-induced intestinal inflammation (Wu et al, 2020). On the other hand, L. reuteri was also reported to maintain the integrity of the gut barrier by upregulating the expression of TJ proteins, evidenced in in preclinical studies (Gao et al, 2022;Liu et al, 2022a;Li et al, 2023a). TJ proteins are primary for epithelial cell proliferation and gut permeability (Kuo et al, 2021).…”
Section: Enhancement Of Intestinal Epithelial Barriermentioning
confidence: 99%